Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Cerita Matematika Pada Siswa SMP - Surbakti, Ari Atmaja; ., Nuryadi; ., Supriyanti (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research began with researchers observing students. Many students find it difficult when working on math story problems. So this research needs to be carried out with the aim of analyzing and describing the causes of students' difficulties in solving story problems. Indicators of difficulty in this research include poor understanding of concepts, difficulty in determining steps to solve story problems, and difficulty in converting story problems into mathematical form. The method used in this research is descriptive qualitative. This is because the data analyzed is descriptive data in the form of spoken or written words and behavior or actions that can be observed. Data collection was carried out based on test results containing story questions and interviews with students. The results of the research concluded that students still had difficulty finding problems and determining the steps to be completed in the problem. Apart from that, students are also less careful in solving math story problems.